A Project-Based View of the Link Between Strategy, Structure and Lean Construction - Jorge Moreira da Costa (2011)
Currently, there is a good understanding that companies do not obtain satisfactoryresults when lean practices are implemented alone. The benefits can only be realizedby making a substantial number of organizational changes, which in turn need to becoherent with the business strategy. However, contextual factors drive companies toadopt different business strategies, organizational structures and bundles ofproduction practices. Consequently, the sequence and content of businessdevelopment projects aimed to implement and test lean construction practices canvary according to each firm's internal characteristics and conjunctural needs.This paper argues that lean implementation is not an isolated event, but part of aneffort to create a strategy-structure alignment. Moreover, because leanimplementation is conducted through different internal projects, it is also argued thatprojects constitute the link between business strategy, organizational structure andlean processes. A model is proposed to explain the role that projects play ininterlinking strategy, structure and processes. In doing so, the authors hope to bringawareness to the bigger changes behind lean implementation and to the challenges ofbuilding "finely-tuned" organizations for specific missions.